1993
DOI: 10.1007/bf01565459
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative treatment of acute medial collateral ligament lesions of the knee joint

Abstract: From 1985 to 1990 102 patients with isolated lesions of the medial collateral ligament of the knee were managed non-operatively with early protected motion and physical therapy. Eighty-six returned to a follow-up examination. The mean follow-up time was 44.2 months. The knees were stable in all but two cases and showed good or excellent results. Ninety-seven percent of the patients returned to their earlier activity level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…The maximal apparent strain during the healing period (2 week: 9.0%, 20 week: 7.2%) was the same as in the intact joint (9.3%), suggesting that the MCL was minimally strained during walking, and that other structures were important in maintaining the proximity of the medial joint surfaces. That favorable strain environment may have contributed to the spontaneous healing of the MCL in these animals, which is also seen clinically after MCL tears in the human knee (Petermann et al, 1993).…”
Section: Tablementioning
confidence: 97%
“…The maximal apparent strain during the healing period (2 week: 9.0%, 20 week: 7.2%) was the same as in the intact joint (9.3%), suggesting that the MCL was minimally strained during walking, and that other structures were important in maintaining the proximity of the medial joint surfaces. That favorable strain environment may have contributed to the spontaneous healing of the MCL in these animals, which is also seen clinically after MCL tears in the human knee (Petermann et al, 1993).…”
Section: Tablementioning
confidence: 97%
“…For collateral ligament injuries, scoring systems to grade severity are often based on millimetres of perceived joint opening with applied manual stress. [1][2][3] The level of resolution required for this may exceed normal levels of human judgement and account for the frequent disparity between laxity examinations and true in-vivo joint function. 4 Quantitative adjuncts, such as stress radiographs, have enabled a more objective measurement of joint space opening, but are still potentially limited by lack of standardisation of the applied load and are susceptible to limb positioning errors as a result of knee flexion or rotation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] This is in contrast to rates of nonunion seen in the medial collateral ligament (MCL), where failure of clinical healing is the exception rather than the rule. [6][7][8][9] The lack of healing seen in the ACL and other intra-articular tissues has been attributed to their relative lack of vascularity, the hostile environment of synovial fluid, 10 to alterations in the cellular metabolism after injury, 11,12 intrinsic cell deficiencies [13][14][15][16][17][18][19][20] the complex biomechanics of these tissues, and cell loss within the tissues after injury. 21 However, recent work has reported that human ACL remnants typically contain viable cells and vasculature, 22 yet there is a gap at the rupture site which remains open.…”
Section: Introductionmentioning
confidence: 99%